Hypothermia inhibits expression of CD11b (MAC-1) and CD162 (PSGL-1) on monocytes during extracorporeal circulation - Swoboda, Stefanie; Grüttner, Joachim; Lang, Siegfried; Wendel, Hans-Peter; Beyer, Martin E.; Griesel, Eva; Hoffmeister, Hans-Martin; Walter, Thomas (In vivo, 2013)
Aim: The aim of the present study was to investigate the effect of different hypothermic temperatures on the expression of cellular adhesion molecules on leukocytes. Materials and Methods: Circulation of blood from six volunteers was performed in an extracorporeal circulation model at 36°C, 28°C and 18°C for 30 minutes. Expression of CD11b, CD54 and CD162 on monocytes was measured using flow cytometry. Results: Expression of CD11b significantly decreased at 18°C and at 28°C compared to 36°C. A significant reduction of CD162 expression was found at 18°C compared to 28°C and 36°C and at 28°C compared to 36°C. No association was found between temperature and expression of CD54. Conclusion: Expression of CD11b and CD162 on monocytes has a temperature-dependent regulation, with decreased expression during hypothermia, which may result in an inhibition of leukocyte-endothelial and leukocyte-platelet interaction. This beneficial effect may influence the extracorporeal circulation-related inflammatory response and tissue damage.
Gesehen am 27.01.2022